(Re)thinking (re)connection: Young people, "natures" and the water–energy–food nexus in São Paulo State, Brazil. Issue 2 (11th November 2018) - Kraftl, Peter; Balastieri, Jose Antonio Perrella; Campos, Arminda Eugenia Marques; Coles, Benjamin; Hadfield‐Hill, Sophie; Horton, John; Soares, Paulo Valladares; Vilanova, Mateus Ricardo Nogueira; Walker, Catherine; Zara, Cristana
Abstract : This paper critically analyses pervasive contemporary discourses that call for children and young people to be "reconnected" with nature and natural resources. Simultaneously, it reflects on emerging forms of nexus thinking and policy that seek to identify and govern connections between diverse sectors, and especially water, energy and food. Both of these fields of scholarship are concerned with connections, of different kinds, and at different spatial scales. Based on a large‐scale, mixed‐method research project in São Paulo State, Brazil, this paper explores how these rather different literatures could be combined in order to (re)think notions of (re)connection that operate across different spatial, political and material registers. Through research with Brazilian professionals and young people about their experiences of, and learning about, the water–energy–food nexus, the paper makes several substantive contributions to scholarship on childhood, youth, environmental education and nexus thinking. Centrally, it is argued that, rather than dispense with them, there are manifold possibilities for expanding and complicating notions of (re)connection, which rely on a more nuanced analysis of the logistical, technical, social and political contexts in which nexuses are constituted. Thus, our work flips dominant forms of nexus thinking by privileging a "bottom‐up" analysis of (especially) young people's everyday, embodied engagements with water, food and energy. Our resultant findings indicated that young people are "connected" with natures and with the water–energy–food nexus, in both fairly conventional ways and in ways that significantly extend beyond contemporary discourses about childhoods–natures (and particularly in articulating the importance of care and community). Consequently, the nexus approach that is advocated in this paper could enable more nuanced, politically aware conceptualisations of (re)connection, both within and beyond scholarship on childhoods–natures and nexus thinking. Abstract : This paper critically analyses pervasive contemporary discourses that call for children and young people to be "reconnected" with nature and natural resources. Simultaneously, it reflects on emerging forms of nexus thinking and policy that seek to identify and govern connections between diverse sectors, and especially water, energy and food. Through research with Brazilian professionals and young people about their experiences of, and learning about, the water–energy–food nexus, the paper flips dominant forms of nexus thinking by privileging a "bottom‐up" analysis of (especially) young people's everyday, embodied engagements with water, food and energy, finding that young people are "connected" with natures and with the water–energy–food nexus, in both fairly conventional ways and in ways that significantly extend beyond contemporary discourses about childhoods–natures (and particularly in articulating the importance of care and community).